Scientific opinion on the tolerable upper intake level for selenium. (20th January 2023) - ,; Turck, Dominique; Bohn, Torsten; Castenmiller, Jacqueline; de Henauw, Stefaan; Hirsch‐Ernst, Karen‐Ildico; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Peláez, Carmen; Pentieva, Kristina; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver a scientific opinion on the tolerable upper intake level (UL) for selenium. Systematic reviews of the literature were conducted to identify evidence regarding excess selenium intake and clinical effects and potential biomarkers of effect, risk of chronic diseases and impaired neuropsychological development in humans. Alopecia, as an early observable feature and a well‐established adverse effect of excess selenium exposure, is selected as the critical endpoint on which to base a UL for selenium. A lowest‐observed‐adverse‐effect‐level (LOAEL) of 330 μg/day is identified from a large randomised controlled trial in humans (the Selenium and Vitamin E Cancer Prevention Trial (SELECT)), to which an uncertainty factor of 1.3 is applied. A UL of 255 μg/day is established for adult men and women (including pregnant and lactating women). ULs for children are derived from the UL for adults using allometric scaling (body weight 0.75 ). Based on available intake data, adult consumers are unlikely to exceed the UL, except for regular users of food supplements containing high daily doses of selenium or regular consumers of Brazil nuts. No risk has been reported with the current levels of selenium intake in European countries from food (excluding food supplements) in toddlers and children, and selenium intake arising from the natural content of foods does not raise reasons for concern. Selenium‐containing supplements in toddlers and children should be used with caution, based on individual needs.